Can process-based modelling and economic valuation of ecosystem services inform land management policy at a catchment scale?. (July 2020) - Lusardi, Jane; Sunderland, Timothy John; Crowe, Andrew; Jackson, Bethanna Marie; Jones, Glyn
Highlights: In practice it is only possible to model and value a minority of ecosystem services. Ecosystem service models need to address changes in habitat condition. Modelling plus valuation needs further development for catchment decision making. Abstract: Land produces a range of benefits, from ecosystem services, but markets only incentivise the production of a small proportion of them. The Ecosystem Approach develops plans for moving towards a more optimal mix. This requires stakeholders to understand the value of ecosystem services and how these values change with land-use and management. We investigate whether process-based modelling and economic valuation can help stakeholders to do this. We do this by applying these tools to a plan to improve ecosystem services delivery in a catchment. To be used in decision-support, analytical approaches need to be relatively inexpensive and rapid, and our analysis was deliberately constrained in this way. Two 25-year future scenarios were developed and compared against a baseline scenario. The first Designated Site scenario was based on enhancing the condition of nationally important nature conservation sites. The second, Ecosystem Services scenario, represented implementing the ecosystem services delivery plan. We modelled the change between the scenarios with an internationally recognised process based ecosystem services toolkit (the Land Use Capability Indicator, LUCI tool) and used the model outputs to inform economic valuation methods. Our selection of which ecosystem services to model and value were initially identified through a participatory approach. However those we could quantify was limited by evidence and data availability. We assessed changes in water quality (phosphorus load), sediment generation, carbon storage and flood regulation. We were able to put economic values on only carbon sequestration and flood regulation. Both the modelling results and the experience of applying the linked modelling-valuation approach are examined in the discussion to consider the limitations to the current usefulness of linking process based modelling to economic valuation for informing land management policy. We explore the origin and nature of these limitations and the key bottlenecks that need to be overcome, applicable to its use in other sites, regions and countries. This includes the availability of suitable coefficients and/or underlying data/evidence to parameterise the model, and the compatibility of model outputs with available economic valuation evidence (for value transfer).